Deciphering Functions of a Putative Histidinol Dehydrogenase in Acidovorax citrulli by Phenotypic and Proteomic Analyses - Yongmin Cho; Haerim Rhyu; Suhyun Lee; Dohyun Kim; Dae Sung Kim; Jisun H. J. Lee; Sang-Wook Han (The Plant Pathology Journal)
Acidovorax citrulli (Ac) is a Gram-negative phytopathogenic bacterium causing bacterial fruit blotch (BFB) on cucurbit crops, specifically in the watermelon industry. However, cultivars of watermelon that are resistant to Ac have not been identified. Therefore, virulence factors/mechanisms in Ac must be characterized to develop alternative control strategies. Functions of a histidinol dehydrogenase, which is an essential enzyme for histidine biosynthesis, remain elusive in Ac. This study aims to elucidate the roles of histidinol dehydrogenase in Ac (HisDAc) using phenotype assays and proteomic analysis. The virulence of a mutant lacking a histidinol dehydrogenase, hisDAc:Tn5(EV), was diminished in geminated-seed inoculation and leaf infiltration assays, and the bacterium was impossible to grow without histidine in minimal media. However, treatment with exogenous histidine completely restored the virulence of the mutant on watermelon and its growth in minimal media, demonstrating that HisDAc is required for histidine biosynthesis, which contributes to virulence and growth. The comparative proteomic analysis indicates that HisDAc is involved in not only amino acid metabolism but also other biological mechanisms, including cell wall/membrane/envelope functions. This suggests that HisDAc may have pleiotropic effects. It was also confirmed that when Escherichia coli was incubated with Ac strains in water, the population level of E. coli increased in the presence of the mutant but not in the presence of the wild-type. This study leads to new insights regarding enzymes related to the production of primary metabolites and provides a promising target to discover an anti-virulence reagent to control BFB.